The Impact of Extrinsic and Intrinsic Motivation towards Job Satisfaction in Finance Service Department of PT. XYZ - Theresia Catharina; Verina Victoria (iBuss Management, 2015)
People are one of the resources that should be managed well by the company. There is no exception for PT. XYZ. As one of the leading FMCG companies in Indonesia and the top 10 global brand, PT XYZ surely has to manage the company well with the support of the employees. One of the ways to keep the performance in the optimum level is by maintaining the job satisfaction of the employees. In order to maintain the job satisfaction, the employees should keep motivated in doing the job. This research is conducted to analyze the impact of intrinsic and extrinsic motivation of employees in Finance Service department of PT. XYZ towards their job satisfaction. Data was gathered using census by distributing questionnaires to 103 employees in Finance Service department of PT. XYZ. The data then analyzed using Multiple Linear Regression analysis. From the research, it can be concluded that overall, the intrinsic and extrinsic motivation of the employees in Finance Service department of PT. XYZ simultaneously have significant impact on employees’ job satisfaction. Keywords: Intrinsic motivation, extrinsic motivation, job satisfaction, Herzberg two-factor theory